THE ROLE OF NOSTALGIA IN MEMORIAL ARCHITECTURE FORMATION Barzani National Memorial in Kurdistan Region as a case study - BARAKAT, ARMANGE ISMAEL; ALI , ALAN FARAYDOON (Journal of Duhok University, 2023)
Determining the concept of nostalgia in architecture and its effect on the architectural formation of the building is considered an essential need to get a complete understanding of the research problem, which is represented by the lack of clarity about the influence of the nostalgia concept on the formation of memorial architecture. One of the fundamental variables of the nostalgia concept is memory. This study defines the concept of nostalgia in architecture as the act of giving physical form to memories. Barzani National Memorial is a place that has an important status in Kurdish memory and has been selected as a case study, which includes a museum, gallery hallway, library, mosque, and an auditorium. The current research adopted qualitative and quantitative methods to collect the required data. Within a graphical analysis and questionnaire, four main variables of nostalgia have been tested: nostalgic memories, nostalgic types, nostalgic return sources, and nostalgic formation. These main variables have sub-variables arranged with their indicators in a form as a tool of measurement. The paper concluded that nostalgic memories and a specific place conjoin to produce the memorial buildings for national exultation, reflect the collective memory, and promote the sense of belonging in society. Considering such a role in nostalgia is essential for achieving memorial architecture.